2022
DOI: 10.1186/s40168-022-01381-1
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota is associated with the effect of photoperiod on seasonal breeding in male Brandt’s voles (Lasiopodomys brandtii)

Abstract: Background Seasonal breeding in mammals has been widely recognized to be regulated by photoperiod, but the association of gut microbiota with photoperiodic regulation of seasonal breeding has never been investigated. Results In this study, we investigated the association of gut microbiota with photoperiod-induced reproduction in male Brandt’s voles (Lasiopodomys brandtii) through a long-day and short-day photoperiod manipulation experiment and feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…Our previous study has shown that pre-treatment for recipient voles might also modify the GO pathways by altering the gut microbiota. [60] We found that increased oxidative damage and inflammation in HG voles is associated with the enriched glycolysis, which is consistent with previous studies that increased oxidative stress and increased inflammation can promote glycolysis of the host. [61] The biological process of sterol synthesis in T-H voles after FMT is significantly different from HG voles.…”
Section: Gut Microbiota May Mediate Aging-related Processes Under Hig...supporting
confidence: 92%
“…Our previous study has shown that pre-treatment for recipient voles might also modify the GO pathways by altering the gut microbiota. [60] We found that increased oxidative damage and inflammation in HG voles is associated with the enriched glycolysis, which is consistent with previous studies that increased oxidative stress and increased inflammation can promote glycolysis of the host. [61] The biological process of sterol synthesis in T-H voles after FMT is significantly different from HG voles.…”
Section: Gut Microbiota May Mediate Aging-related Processes Under Hig...supporting
confidence: 92%
“…Although this analytic strategy excluded taxonomic units identified to only phylum, class, or order level, the diversity estimated via the Shannon Index was comparable to earlier data from this species [ 15 , 18 ]. As in other studies from rodents and primates [ 19 , 20 , 21 , 22 , 23 ], Firmicutes and Bacteroidetes were the most abundant phyla, although the relative amount of Bacteroidetes was lower in the hamsters of the present study [ 12 , 14 , 18 , 19 ]. Furthermore, the Ulm hamsters’ microbiome contained a similar amount of Proteobacteria when compared to other Djungarian hamsters and other rodents, ranging from 2 to 10% [ 12 , 14 , 18 , 20 , 21 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 77%
“…Genus Prevotella and genus Alistipes were enriched in the breeding season, genus Oscillibacter , order Lactobacillales, family Lachnospiraceae, and family Ruminococcaceae were enriched in the non-breeding season. In a previous study, Prevotella and Alistipes were enriched in Brandt’s voles ( Lasiopodomys brandtii ) with long photoperiods [ 22 ], which were reflected in the present study for the breeding season. Alistipes were positively correlated with cholesterol metabolism [ 66 ], which may be related to the high-fat, high-protein diet structure of breeding muskrats.…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile, several studies have confirmed that many other factors, such as estrogen, thyroid hormone, kisspeptin, and living environment, affect seasonal breeding animals [ 18 , 19 , 20 , 21 ]. According to a recent study, the gut microbiota may regulate seasonal breeding and behavior based on photoperiodic timing in rodents via the Hypothalamic Pituitary Gonadal (HPG) axis, melatonin, and the Kisspeptin/G-protein coupled receptor 54 (GPR54) system in the hypothalamus [ 22 ]. This report has aroused our interest in the further investigation of the association between gut microbiota and seasonal breeding.…”
Section: Introductionmentioning
confidence: 99%